2022
DOI: 10.1186/s12889-022-14349-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental and physical health and well-being of Canadian employees who were working from home during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has drastically changed various aspects of our lives, including how we work. Since the start of the pandemic, numerous organizations in Canada have mandated their employees to work from home (WFH) on a full-time basis. The rapid rise in the number of remote workers and the possibility for WFH continuing in the future signifies the importance of understanding the health and well-being of employees working from home over the course of the pandemic in Canada. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Our study is novel in that it was conducted following earlier containment measures and allowed the assessment of specific medium/long-term effects of WH on health-related variables. Another survey conducted among Canadian adults who worked from home during the COVID-19 pandemic found a reduction in the levels of stress and burnout, as well as a decline in general mental health over time [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study is novel in that it was conducted following earlier containment measures and allowed the assessment of specific medium/long-term effects of WH on health-related variables. Another survey conducted among Canadian adults who worked from home during the COVID-19 pandemic found a reduction in the levels of stress and burnout, as well as a decline in general mental health over time [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…As research into teleworking becomes more galvanized, it becomes clear that this new work paradigm entails a variety of physical, emotional, and social symptoms, which can affect the quality of life, health, and performance of workers [ 76 , 92 ]. Regarding the third research question, we can divide the symptoms into two large groups: (1) ergonomic and musculoskeletal, essentially due to the lack of adequate ergonomic conditions and a sedentary lifestyle; and (2) psychological symptoms, such as anxiety, stress, and anguish, closely related to the lack of work–life balance.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also showed that teleworking can have mixed impacts [ 67 ] regarding workers’ quality of life and health. In more critical circumstances, pathological manifestations tend to be aggravated by the action of a set of other variables, which include work characteristics [ 76 ], professional profiles, work quality standards, the support received from employers, personal preferences [ 9 , 56 , 75 , 78 ], and family structure [ 79 , 81 , 92 ]. It is also important to highlight that the impacts of working from home vary according to gender [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the organisational point of view, employees were said to be affected to a higher extent as the organisations ( [3]). In a study conducted by ( [12]), the researchers found out that in the beginning, employees were more prone to mental and physical health deterioration such as stress and burnout which eventually decreased overtime. The researcher also specified that when the organisations understand the negative impacts of work from home, they can establish better strategies to minimise the negative impacts.…”
Section: Review Of Literaturementioning
confidence: 99%